Magnetic nano-particles for protein purification : supplementary equipment project - Tan, Kam Chiu. (2008)
Magnetic nanoparticles (MPs) were synthesized using the co-precipitation method, with methyl acrylic acid - ethyl acrylate (MAA-EA) microgels as the colloidal scaffold. The MAA-EA microgel was prepared using the emulsion polymerization method with di-ally1 phthalate (DAP) as the crosslinker. The composition of the microgel used was 50-50-4, denoting a 50 mole% of MAA; 50 mole % of EA and a 4 wt% of DAP. Characterisation of the microgel and MPs were conducted using techniques such as potentiometric titration, dynamic light scattering (DLS) and zeta potential (Z.P) as a function of pH. The Vibrating Sample Magnetometer (VSM), Thermogravimetric Analysis (TGA), and Transmission Electron Microscopy (TEM) were employed to further characterize the MPs. A new hybrid multilayer coated magnetic nanoparticles (MNPs) was synthesized by the co-precipitation of magnetite inside a colloidal scaffold comprising of methacrylic acid- ethylacrylate nanogels(MAA-EA). Multilayer coating was assembled by depositing alternating layers of polyelectrolytes, poly(allylamine hydrochloride) (PAH) and poly(sodium 4-stryrenesulfonate) (PSS), on the MNPs. Designing of surface charge on MNPs to suit application was demonstrated using the multilayer coating methodology. In addition, we discovered that colloidal scaffold containing grafted PEG chains was required as steric stabiliser on MNPs to prevent bridging flocculation during the multilayer coating process. The MNPs are colloidally stable with high magnetite content of up to 74 wt%, and high superparamagnetic properties (70emu/g without hysteresis). The hydrodynamic radius (&) of MNPs exhibited pH responsiveness where swelling from 120 to 180 nm occurred in the pH range of 4 to 9. The interaction of MPs and model molecules were examined using the various characterisation techniques. Recovery of magnetic particles as well as separation of captured molecules was conducted using the High Gradient Magnetic Separator (HGMS).